Danazol increases T regulatory cells in patients with aplastic anemia. Issue 8 (14th September 2018) - Khurana, Harshit; Malhotra, Pankaj; Sachdeva, Man Updesh; Varma, Neelam; Bose, Parveen; Yanamandra, Uday; Varma, Subhash; Khadwal, Alka; Lad, Deepesh; Prakash, Gaurav
ABSTRACT: Objectives: Danazol is an attenuated androgen and is used in the treatment of aplastic anemia (AA) in resource constraint settings. We chose to study the role of CD4+ CD25 high CD127 low FoxP3+ T regulatory cells (T-regs) in the pathophysiology of AA and their response to treatment with Danazol alone or in combination with immunosuppressive treatment (IST). Methods: T-regs' percentages of 25 acquired idiopathic AA patients and 25 healthy controls who completed study protocol were analyzed by performing multicolor flowcytometry on peripheral blood samples. Results: More than one-third (36%) of AA patients in our study received Danazol as monotherapy, whereas less than a third (32%) each received standard doses of IST with equine Anti Thymocyte Globulin (ATG) and Cyclosporine combination, or Cyclosporine and Danazol combination, respectively. Results showed that all AA patients had a significantly lower percentage of T-regs at the time of diagnosis when compared to healthy controls ( p  < 0.0001), implicating their role in the pathophysiology. On treatment, all 25 patients showed a significant rise in the percentage of T-regs when compared to baseline ( p  < 0.0001). Discussion: The rise in T-regs' percentage was higher in patients treated with Danazol alone when compared to standard IST (ATG with Cyclosporine), or Cyclosporine with Danazol combinations ( p  = 0.585). Conclusion: We conclude that Danazol also leads to increase in T-regs in acquired idiopathic AA.